Education Programs in Post-Conflict Environments: a Review from Liberia, Sierra Leone, and South Africa - Hernando Barrios-Tao; José María Siciliani-Barraza; Bibiana Bonilla-Barrios (Revista Electrónica Educare)
Education should be considered as one of the mechanisms for governments and nations to succeed in a post-conflict process. The purpose of this Review Article is twofold: to explain the importance of education in a post-conflict setting, and to describe a few strategies that post-conflict societies have implemented. In terms of research design, a multiple case study approach has been implemented. The paper reviews a unique topic with specific reference to education plans implemented in post-conflict societies such as Liberia, Sierra Leone, and South Africa. Each of them has experienced violent conflicts and has used education as a tool to succeed in their post-conflict process. In sum, there are several educational programs that involve children, young people, survivors, parents, teachers, and local communities as well as curriculums focused on teaching of cultural values and technical skills to improve the quality of life in a post-conflict setting.